Proyecto de creación de una empresa en el área de asesoría de bienes raices para estudiantes universitaríos de otras provincias en la ciudad de Guayaquil - Vega Honores, Carmen Lilibeth (2010)
Currently the migration of young college students to the city of Guayaquil is having a considerable growth due to several reasons; among them are the classification of universities around the country and the free education at senior level. This project is based primarily on meeting the needs of students from the provinces of El Oro and Manabi who want to do university studies in the city of Guayaquil, it provide counseling service of real estate, it means suggestions for your stay, letting them know the different kind of apartments, houses, buildings, hostels available to be rent with their respective internal and external physical characteristics showing them by photographs, and letting them know the address, price, warranty payments. The main objective is to save money on mobilization, food and time for students from other provinces who have to travel to Guayaquil to find housing. To make easy the rental process for both the landlord and the tenant to provide security and compromise.